Events Management. - Bowdin, G. A. J.; Bowdin, G. A. J. (2023)
An introductory text focusing on events planning and management, the fourth edition of 'Events Management' provides a complete A to Z of the principles and practices of planning, managing and staging events.
Previous edition: published as by Glenn A.J. Bowdin, Johnny Allen, William O'Toole, Robert Harris, Ian McDonnell. Amsterdam: Butterworth-Heinemann, 2011.
Includes online support material.
Includes bibliographical references and index.
Keywords: Special events -- Great Britain -- Management; Customs and Folklore